1984
DOI: 10.1113/expphysiol.1984.sp002810
|View full text |Cite
|
Sign up to set email alerts
|

CONTROL OF CULTURED EPITHELIAL (MDCK) CELL TRANSPORT FUNCTION: IDENTIFICATION OF a Β‐ADRENOCEPTOR COUPLED TO ADENYLATE CYCLASE

Abstract: SUMMARYA catecholamine-sensitive adenylate cyclase activity was observed in cell homogenates of cultured renal epithelial (MDCK) cells. 10 4UM isoprenaline gave a 2-85-fold increase in adenylate cyclase activity above basal levels. A series of adrenoceptor agonists gave a relative ptoency series of isoprenaline > adrenaline > noradrenaline (K values of 19 x 10-7, 16 x 10-6 and 19 x l0-, M respectively), consistent with activation of a fl-adrenoceptor. Intracellular accumulation of cyclic AMP was also stimulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

1986
1986
1996
1996

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 22 publications
(37 reference statements)
2
13
0
Order By: Relevance
“…Hassid (1983) in particular has demonstrated that exogenous PGE2 stimulates intracellular cyclic AMP accumulation in the presence of IBMX; in the present experiments, using MDCK cells of a defined phenotype (Rugg & Simmons, 1984b), this finding has been confirmed. In addition it appears that the response is relatively specific for the prostaglandin E series.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Hassid (1983) in particular has demonstrated that exogenous PGE2 stimulates intracellular cyclic AMP accumulation in the presence of IBMX; in the present experiments, using MDCK cells of a defined phenotype (Rugg & Simmons, 1984b), this finding has been confirmed. In addition it appears that the response is relatively specific for the prostaglandin E series.…”
Section: Discussionsupporting
confidence: 77%
“…Data is presented that suggest that PGE1, most probably via generation of intracellular cyclic AMP, stimulates an inwards short-circuit current in voltage clamped MDCK epithelial layers mounted in Ussing chambers, consistent with basal to apical Cl-secretion and not with an inhibition of Na+ absorption. Preliminary communications of some of the present findings have been published (Simmons, 1981a;Rugg & Simmons. 1984a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…VIP activates renal adenylate cyclase and the pattern of VIPstimulated adenylate cyclase along the rabbit nephron is unique amongst renal-acting hormones (Griffiths et al 1988a). (Rugg & Simmons, 1984;Griffiths & Simmons, 1987). Renal cortical homogenates from cat, dog and human renal cortex from nephrectomy samples (performed, in humans, for therapeutic reasons) were prepared for comparative purposes as described previously (Griffiths & Simmons, 1987 ,1 ofI M-HCI.…”
Section: Introductionmentioning
confidence: 99%
“…1 1) was determined using L-leucine-p-nitroanilide as substrate in a 0 1 M phosphate buffer (pH 7-2). Adenylate cyclase activity was measured exactly as described by Rugg & Simmons (1984), except that the final incubation pH was 7-5. Maximal activity of the catalytic unit was taken as that activity (minus basal levels) stimulated by 100/uM-forskolin.…”
Section: -2mentioning
confidence: 99%